PEMBELAJARAN BIOLOGI BERORIENTASI LIFE SKILL UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA SMA KARTIKATAMA METRO - Muhfahroyin, Muhfahroyin (UNIVERSITAS MUHAMMADIYAH METRO, 2010)
The objective of this research are to increase the student activities andÂ learningÂ achievement in Biology Learning. This Research conducted using Classroom Action Research two cycles. The result of this research shows that life skills oriented biology learning contributed the increase of studentsâ activities and their learning achievement. It can be seen fromÂ the increase of studentsâ learning activities from 67,5% in cycle IÂ toÂ 91% cycle II.Â Contextual Teaching and Learning (CTL) approach also able to increase the student achievements. In cycle I, the average score of student is 70,53 increasing to 79,83. Â From this research, the researcher suggest that Contextual Teaching and Learning (CTL) approach should be applied, especially to integrate the values of IMTAQ in Biology learning and other subject